Causes and Solutions for Students with Declining Academic Performance - Siribowonkul, Naphat; Kunarak, Pragob (Journal of Dhamma for Life, 2025)
This research aimed to investigate: (1) the relationship of factors influencing the decline in students’ academic performance, and (2) the approaches to improve students’ academic achievement. The sample consisted of 165 students. A questionnaire was employed as the main research instrument, together with in-depth interviews with 5 experts. The statistical methods used for data analysis included percentage, mean, standard deviation, multiple regression analysis, and content analysis. The findings revealed that: (1) students’ learning behavior, effective instructional methods, and other relevant factors could predict students’ learning effectiveness by 65.00%; (2) the strategies to enhance students’ academic performance were as follows: (a) stimulating learners’ interest through educational games and active learning, (b) creating an engaging learning environment, (c) posing questions that foster curiosity, (d) providing encouragement and building confidence, (e) implementing performance-based assessment and evaluation, (f) promoting parental involvement in supporting learning, and (g) developing social skills and emotional regulation.